REGIONAL DEVELOPMENT OF TOURISM IN BULGARIA – THE CONTRIBUTION OF HALLMARK EVENTS - Ivanova, Petya; Naydenov, Lyudmil; Filipova, Milena (Revista Inclusiones, 2021)
This article aims to study theoretically and empirically the state and trends in the development of tourism regions and the potential of the hallmark events for a complex attractive and competitive regional tourism product and regionalized marketing in Bulgaria. The object of study are the tourism regions in the Republic of Bulgaria, according to the Concept for Tourism Zoning - Danube, Stara planina, Rose valley, Thrace, Rila and Pirin, Varna (North Black Sea Coast), Burgas (South Black Sea Coast), Rhodopes, Sofia. The subject of study are the trends in their development and event tourism as part of their management strategy. Interdisciplinary methodology was used in the study – inductive and deductive approach, the method of analysis and synthesis, the statistical approach in studying phenomena and the Delphi method. The content, situational and comparative analysis was performed, using a set of techniques applicable to the respective object of the study and related to the goal set. As a result of the conducted analysis some conclusions can be drawn according: the conditions in regional tourism in Bulgaria; rate of change of tourism indicators by tourism regions; opportunities for strategic management of hallmark events for achieving destination competitiveness for each one of them. Received results serve as an evidence that with pursuing a purposeful policy hallmark events of every tourist region can form its competitive identity. The outcomes of the study can be used in updating the planning documents at the national level, as well as in implementing the strategic management by the Organizations for Tourism Region Management.